Physicochemical Kinetic Evaluation and Biological Activities of Wild Horsetail Extract - Baydaa Awad Kadhim; Fouad Razzaq Al-Burki; Assel Majeed Hammeed (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
The objective of this study is to evaluate the physicochemical, kinetic and bioactive characteristics of the alcoholic extract of Wild Horsetail. The total amount of phenolic and flavonoid was calculated and the antioxidant capacity was evaluated with the help of DPPH and ABTS tests. Potential for antidiabetic ability was also studied through the inhibition of alpha-amylase as well as alpha-glucosidase. In addition, the kinetics of trapping DPPH free radicals were studied. The chemical analysis revealed the presence of a variety of bioactive compounds, the major one being scoparone (26.45%) followed by phytol (7.43%) and methyleugenol (6.52%). Also, the total phenolic and flavonoid contents exhibited high amounts, specifically, 186.43 ± 4.18 mg gallic acid equivalent/g extract and 97.87 ± 2.66 mg quercetin equivalent/g extract, respectively. The extract displayed antioxidant capacity with IC50 of 71.37 ± 2.16 and 58.42 ± 1.87 µg/ml in DPPH and ABTS test respectively. It also showed significant inhibition of alpha-amylase and alpha-glucosidase enzymes with IC50 values of 92.78 ± 2.34 and 68.54 ± 1.92 µg/ml respectively. Based on the kinetic study, it was found that the DPPH free radical scavenging activity was described by a pseudo-first-order kinetic model. As a confirmation of the wild horsetail's phenolic and flavonoid content, ethanolic extract has a high concentration. These compounds have antioxidant ability and modulating effect on enzymes related to carbohydrate metabolism which can be incorporated into natural formulations. Such preparations can be used in pharmaceuticals and as dietetic supplements to prevent oxidative stress and assist in the treatment of diabetes.